The unusual properties of lactoferrin during its nascent phase - Sara Notari; Giorgia Gambardella; Federica Vincenzoni; Claudia Desiderio; Massimo Castagnola; Alessio Bocedi; Giorgio Ricci (Scientific Reports, 2023)
Abstract Lactoferrin, a multifunctional iron-binding protein containing 16 disulfides, is actively studied for its antibacterial and anti-carcinogenic properties. However, scarce information is nowadays available about its oxidative folding starting from the reduced and unfolded status. This study discovers unusual properties when this protein is examined in its reduced molten globule-like conformation. Using kinetic, CD and fluorescence analyses together with mass spectrometry, we found that a few cysteines display astonishing hyper-reactivity toward different thiol reagents. In details, four cysteines (i.e. 668, 64, 512 and 424) display thousands of times higher reactivity toward GSSG but normal against other natural disulfides. The formation of these four mixed-disulfides with glutathione probably represents the first step of its folding in vivo. A widespread low pK a decreases the reactivity of other 14 cysteines toward GSSG limiting their involvement in the early phase of the oxidative folding. The origin of this hyper-reactivity was due to transient lactoferrin-GSSG complex, as supported by fluorescence experiments. Lactoferrin represents another disulfide containing protein in addition to albumin, lysozyme, ribonuclease, chymotrypsinogen, and trypsinogen which shows cysteines with an extraordinary and specific hyper-reactivity toward GSSG confirming the discovery of a fascinating new feature of proteins in their nascent phase.